2019
DOI: 10.1111/irv.12630
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus shedding reduction observed at 12 weeks post‐vaccination when newborn pigs are administered live‐attenuated influenza virus vaccine

Abstract: Background Influenza A virus in swine ( IAV ‐S) causes an acute respiratory disease of swine which results in great economic losses. A bivalent H1N1 and H3N2, NS 1‐truncated live‐attenuated IAV ‐S vaccine ( LAIV , Ingelvac Provenza ™ ) has recently become available. Objective Reduction of shedding during an outbreak in the nursery or fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Shortly after LAIV administration, LAIV was detected in the vaccinated pigs which was expected since the vaccine virus is live and capable of replication despite being attenuated. LAIV was also detected for up to 6 days post-vaccination, and duration of LAIV shedding in this study was similar to other studies with this vaccine under experimental conditions [29] and mimics the duration of shedding described for pigs challenged with wild-type IAV in IAV inoculation studies [30]. Furthermore, we were able to isolate LAIV from vaccinated pigs indicating presence of replicating virus and we confirmed through whole genome analysis that all the IAV isolates recovered during the study were of LAIV origin.…”
Section: Discussionsupporting
confidence: 90%
“…Shortly after LAIV administration, LAIV was detected in the vaccinated pigs which was expected since the vaccine virus is live and capable of replication despite being attenuated. LAIV was also detected for up to 6 days post-vaccination, and duration of LAIV shedding in this study was similar to other studies with this vaccine under experimental conditions [29] and mimics the duration of shedding described for pigs challenged with wild-type IAV in IAV inoculation studies [30]. Furthermore, we were able to isolate LAIV from vaccinated pigs indicating presence of replicating virus and we confirmed through whole genome analysis that all the IAV isolates recovered during the study were of LAIV origin.…”
Section: Discussionsupporting
confidence: 90%
“…Ingelvac Provenza (Boehringer Ingelheim, St. Joseph, MO, USA), which is a bivalent product containing two reverse genetic generated LAIVs: one cluster I H3N2 virus based on A/swine/Texas/4199-2/1998 with the NS1 truncation and one virus containing the same attenuated internal gene cassette derived from the H3N2 strain but with the HA and NA derived from a γ2 beta-like H1N1 strain (A/swine/Minnesota/37866/1999). This vaccine was efficacious in reducing virus nasal shedding after challenge with heterologous strains, either H1N1 or H3N2, with and without presence of MDAs (113,114). However, a recent phylogenetic study done in the US with samples collected in 2018 found reassortant strains containing LAIV vaccine strain genes in combination with US endemic field strain genes (115).…”
Section: Attenuation By Non-structural Ns1 Protein Truncationmentioning
confidence: 98%
“…Ingelvac Provenza (Boehringer Ingelheim, St. Joseph, MO, USA) is a bivalent LAIV containing one cluster I H3N2 virus based on TX/98 with the NS1 truncation and one virus containing the same backbone but with the HA and NA derived from a g2-b-likeH1N1 strain (A/swine/Minnesota/37866/1999), that no longer circulated when the LAIV became available. This vaccine was efficacious in reducing virus nasal shedding after challenge with heterologous strains, either H1N1 or H3N2 (Genzow et al, 2018;Kaiser et al, 2019). However, a phylogenetic analysis of whole genome sequences carried out in the US using samples obtained in 2018 indicated that reassortment strains containing LAIV genes in combination with genes from endemic field strains circulating in US were generated (Mancera Gracia et al, 2020;Sharma et al, 2020), which suggests a substantial degree of LAIV replication.…”
Section: Swine Influenza Virus (Siv)mentioning
confidence: 99%